Kinetic Modeling of Ethylbenzene Isomerization using Bodenstein Approximation Technique - Kolo, A. S.; Grema, A. S.; Maina, I. I. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
Ethylbenzene isomerization reaction is a significant reaction employed in the production of xylene isomers which are used as petrochemical feedstocks. The reaction which proceeds over Pt/Al2O3 catalyst is multi-pathway and multi-cycle in topology. Kinetic model for the reaction was developed in this study using the general rate equation approach. Bodenstein approximation, cross-to-square, and Y-to-delta transformation techniques were used to reduce the complex reaction network to a single cycle network. In addition, the general rate equation for reduced single cycle networks was applied to derive the model for the reaction. The Nelder-Mead simplex optimization technique was used to estimate the kinetic parameters in the model. The structure of the model developed indicates that the model reasonably represents the mechanism of the reaction although few anomalies were observed in the values of the kinetic parameters estimated. The activation energy obtained for the rate constants follows the expected trend for multi-step reactions.